Analisis Disiplin Kerja dan Budaya Organisasi Terhadap Kinerja Karyawan, Serta Komitmen Organisasi Sebagai Variabel Intervening (Studi Empirik Karyawan Bank BTN Cabang Cilegon, Banten) - Apriyanti, Lenny; Khurosani, Aan (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2018)
The world of banking business today is very competitive competition. Therefore, the company must make appropriate business strategy changes so as not to lose competitiveness with other companies. Changes in strategies undertaken aims to improve the performance of the company, one of the changes namely human resources. This study aims to explain the effect of work dicipline and organizational culture on work performance and organizational commitment as an intervening variable at the bank BTN branch Cilegon. The study was conducted by taking samples using the method used in this sampling is a saturated or census sampling. saturation or census sampling is a sample determination technique when all members of the population are used as a sample. Data collection was obtained from 86 employees of Bank BTN Cilegon branch by providing questionnaire consisting of questions and statements. Respondents' answers to questions and statements were analyzed qualitatively and quantitatively, and the answers were analyzed by analytical technique method using SmartPLS version 2.0.m3. The result of analysis shows that the direct effect of work discipline on work performance is positive and significant. and the direct influence of organizational culture on work performance is positive and significant. then work discipline towards organizational commitment is positive and significant. Organizational culture of organizational commitment is positive and significant. and organizational commitment to work performance is positive and significant.